Extensive hepatectomy preserving segments IV and I in the treatment of multiple metastases from a colon carcinoid - González, Daniel; Rodríguez, Gustavo; Plazzotta, Cecilia; Balboa, Oscar (Cirugía del Uruguay, 2006)
Clinical case of extensive hepatectomy for curing purposes, of mu/tiple metastases of carcinoid tumor and survival free of disease for 57 months. lt should be highlighted that this procedure was rendered possible due to the slow evolution characterizing this type of metastases as well as to the fact that it was favored by compensatory hipertrophy determined by hydatid liver cyst. This condition has high incidence in our country. There are no reports in international literature of a similar association.